2013
DOI: 10.4236/as.2013.412107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci associated to agronomic traits and yield components in a <i>Sorghum bicolor</i> L. Moench RIL population cultivated under pre-flowering drought and well-watered conditions

Abstract: The present study aims to identify QTL influencing agronomic traits and yield components under well-watered and pre-flowering drought stress conditions. One hundred F 5 recombinant inbred lines (RIL) and the parental lines of a cross between a drought-tolerant and a susceptible line in a field experiment were carried out at Nong Lam University of Ho Chi Minh City, Vietnam. Drought stress was induced by withholding irrigation water from the plants at four weeks after sowing to flowering. Leaf area of the third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…Additionally, we identified one SNP aligning to sorghum chromosome 6 that was significantly associated with stem diameter when we corrected for the environmental influence of latitude. The stem diameter SNP was near two previously identified QTLs for stem diameter in sorghum (Shiringani et al, 2010;Phuong et al, 2013). We also identified one SNP on chromosome 3 that was significantly associated with stem height (corrected for latitude), and was near a previously identified sorghum QTL for plant height (Phuong et al, 2013).…”
Section: Snp-trait Associationssupporting
confidence: 54%
See 1 more Smart Citation
“…Additionally, we identified one SNP aligning to sorghum chromosome 6 that was significantly associated with stem diameter when we corrected for the environmental influence of latitude. The stem diameter SNP was near two previously identified QTLs for stem diameter in sorghum (Shiringani et al, 2010;Phuong et al, 2013). We also identified one SNP on chromosome 3 that was significantly associated with stem height (corrected for latitude), and was near a previously identified sorghum QTL for plant height (Phuong et al, 2013).…”
Section: Snp-trait Associationssupporting
confidence: 54%
“…The stem diameter SNP was near two previously identified QTLs for stem diameter in sorghum (Shiringani et al, 2010;Phuong et al, 2013). We also identified one SNP on chromosome 3 that was significantly associated with stem height (corrected for latitude), and was near a previously identified sorghum QTL for plant height (Phuong et al, 2013). Heritability as estimated from SNP data was 0Á33, 0Á81 and 0Á71 for stems per area, stem height and stem diameter, respectively.…”
Section: Snp-trait Associationssupporting
confidence: 51%
“…QTLs for grain yield in sorghum in combination with drought tolerance or cold tolerance or yield components (Kapanigowda et al, 2014;Nagaraja Reddy et al, 2013;Phuong et al, 2013;Rama Reddy et al, 2014;Sabadin et al, 2012). In addition, physiological parameters for leaf greenness (chlorophyll content and chlorophyll fluorescence) are reported to be positively correlated with grain yield under normal and drought conditions in wheat (Lopes and Reynolds, 2012;Pinto et al, 2010;Thomas and Smart, 1993) and sorghum (Harris et al, 2007;Xu et al, 2000a).…”
Section: Researchmentioning
confidence: 99%
“…Given the conservation of gene function among closely related cereal species, this presents opportunities for comparative genomics studies to investigate the genetics of grain size in other cereal crops using knowledge gained from gene cloning studies in maize and rice. The sorghum QTL atlas of Mace et al () details around 100 grain weight QTL in sorghum that have been identified through linkage analysis in 18 studies (Bai et al , ; Boyles et al , ; Brown et al , ; Feltus et al , ; Gelli et al , ; Han et al , ; Mocoeur et al , ; Murray et al , ; Paterson et al , ; Phuong et al , ; Rajkumar et al , ; Rami et al , ; Reddy et al , ; Shehzad and Okuno, ; Spagnolli et al , ; Srinivas et al , ; Tao et al , ; Tuinstra et al , ). A further 12 markers associated with grain weight have been identified in three GWAS studies (Boyles et al , ; Upadhyaya et al , ; Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%